Synthesis of hydroxyapatite through dry mechanomical method and its conversion to dense bodies: preliminary result - Iis, Sopyan (Springerlink, 2011)
Hydroxyapatite (HA) powder has been prepared through mechanochemical synthesis from a dry powder mixture of calcium hydroxide Ca(OH)2 and di-ammonium hydrogen phosphate (NH4)2HPO4. Three different rotation speeds of 170 rpm (M1), 270 rpm (M2) and 370 rpm (M3) were used in this method. The as synthesized powder analyzed by FTIR and XRD confirmed the formation of HA structure with nano crystallite size in all milling speeds. XRD results showed the wide broad peaks of HA powders narrowed and crystallinity increased (31.0-42.5%) when the milling speed was accelerated to 370 rpm. The powders were compacted using cold isostatic pressing at 200 MPa and then subjected to 1150oC, 1250oC and 1350oC sintering. The sintered compacts were mechanically tested by Vickers microhardness indentation method. Powder synthesized at 370 rpm was found to have a significant hardness, 5.3 GPa obtained after 1250oC sintering.